Design and implementation of an EEG system as well as a physiographer for monitoring psychological treatments within the faculty of psychology of the Antonio Nariño University headquarters Cartagena - Juan Vicente Cajal-Barros (Sostenibilidad, Tecnología y Humanismo, 2018)
The project designed and implemented was an EEG as the first part of a macro project, which allowed the integration between the different programs of ANTONIO NARIÑO University. This system is an integral part of the physiographer, conditioning circuits, filters, amplifiers, a data acquisition system and a virtual instrument were designed that capture the variables through a data acquisition card to be analyzed and visualized dynamically on a personal computer. Design and implementation process were divided into 5 modules. It will begin describing magnitudes to be measured, the sensors that will give us a better capture of our signals, the next two modules are the circuitry and the patient protection, to finish with data acquisition and the visualization in a personal computer.